Uroguanylin regulates net fluid secretion via the NHE2 isoform of the Na+/H+ exchanger in an intestinal cellular model - Toriano, Roxana Mabel (2011)
Uroguanylin (UGN) has been proposed as a key regulator of salt and water intestinal transport. Uroguanylin (UGN) activates cell-surface guanylate cyclase C receptor (GC-C) and modulates cellular function via cyclic GMP (cGMP), thus increasing electrolyte and net water secretion. It has been suggested that the action of UGN could involve the Na+/H+ exchanger, but the actual contribution of this transporter still remains unclear. The objective of our study was to investigate the putative effects of UGN on some members of the Na+/H+ exchanger (NHE) family, as well as to clarify its consequences on transepithelial fluid flow in T84 cells. In order to do so, transepithelial fluid flow (Jv) was studied by optic techniques and intracellular pH (pHi) was measured with a fluorescence method. Results showed that NHE2 is found at the apical membrane and has a major role in Na+ absorption; NHE1 and NHE4 are localized at the basolateral membrane with a house-keeping role in steady state pHi. Cell exposure to apical UGN increases net secretory Jv, without changing short-circuit currents nor transepithelial resistance, and reduces NHE2 activity. Therefore, at physiological pH, the effect on net Jv was produced mainly by a reduction in normal Na+ absorption through NHE2, rather than by the stimulation of electrolyte secretion. Our study shows that the effect of UGN on pHi is GC-C/cGMP-mediated and enhanced by sildenafil, thus involving PDE5 enzyme. Additionally, cell exposure to apical UGN results in intracellular alkalinization, probably due to indirect effects on basolateral NHE1 and NHE4, which have a major role in pHi regulation.